A comparison of the anticipated and pharmacological effects of alcohol on cognitive bias, executive function, craving and ad-lib drinking. (January 2013) - Christiansen, Paul; Rose, Abigail K; Cole, Jon C; Field, Matt
Acute alcohol administration alters automatic processing of alcohol-related cues, impairs executive functions and increases alcohol seeking. Few studies have investigated the effects of expecting to receive alcohol on these measures. Thirty-one social drinkers completed three experimental sessions receiving either 0.65 g/kg alcohol, a placebo and a control beverage (which they knew was not alcoholic) before reporting craving and completing a test battery including a measure of automatic alcohol-approach tendencies (stimulus response compatibility task), a measure of executive function (Controlled Oral Word Association Task (COWAT)) and a taste test assessing ad-lib drinking. Results indicated that alcohol administration impaired performance on the COWAT and increased ad-lib drinking; however, there were no significant differences on these measures after administration of placebo versus control beverages. Craving was increased after alcohol and (to a lesser extent) after placebo. Automatic alcohol-approach tendencies were pronounced after both alcohol and placebo compared to the control beverage, with no difference between alcohol and placebo. Results suggest craving is sensitive to the anticipated and pharmacological effects of alcohol, alcohol-approach tendencies are particularly sensitive to the anticipated effects of alcohol, and measures of executive function and ad-lib drinking are affected by the pharmacological, but not the anticipated, effects of alcohol.